Sports Massage - Mills, Ramela; Parker-Bennett, Shanon (London : Heinemann, 2004)
Written specifically for certificate level, anatomy, physiology and health and safety are covered in addition to massage technique. The text is suitable for candidates taking the Sports Massage option as part of the BTEC National Sports Studies qualification as well as for VTCT candidates.
Includes index.
Keywords: Sports massage; Health and Fitness